Fabrication of vascularized hydrogel construct through 3D printing - Neo, Frederik Wang Huang (2018)
Tissue Engineering is an interdisciplinary field that includes the mechanical, electrical, computer and biological engineering aspects of study in developing solutions for tissue creation and repair through transplantation and implants. It is an advanced field of research that currently takes advantage of 3D printing which itself has been touted as a revolutionary manufacturing method that possibly disrupts how manufacturing is viewed and done. The ability to convert a virtual model to a physical one through 3D printing has revolutionized and opened up a whole slew of new avenues in the manufacturing process of 3D scaffolds for tissue engineering purposes. Because it is still a relatively new field of study and research that is far from reaching its projected potential, tissue engineering currently receives an overwhelming amount of interest in the field as researchers strive to constantly push its boundaries due to its exciting prospects. Vasculature is a term that denotes the blood vessels and capillaries of an organ. Thus, vascularization in this case is the process of forming a distributed network of blood vessels much like that of a functional living organ, the purpose being to disseminate essential oxygen and nutrients in order for the cells to remain alive and functioning. This project aims to investigate and show a possible avenue of approach where a photopolymerizable hydrogel structure of choice with an internally enclosed uniquely-designed vascularized network is able to be easily and consistently produced using readily obtainable materials. Fused Deposition Modelling(FDM) was selected as the 3D Printing method of choice due to its comparative ease of usage, accessibility and open-sourced system nature, as well as the variety of materials available. PVA was the material of choice due to constraining factors. A PVA complex CAD network of blood vessels was 3D printed out, encased in a PEGDMA+Irgacure 2959 solution, then inserted into an UV environment for curing. Since PVA is used, water was added for dissolving and eventually the removal of the internal PVA, creating and mimicking a network of blood vessels, creating “channels” which allow for flow and subsequently cell culture, where possibly differing types of cells on separate occasions, were cultured through the channels. This sufficiently shows that the above route undertaken to produce a hydrogel enclosed network can be utilised for further studies in the field of cell culture.